Distal transradial access for cardiac catheterization: A systematic scoping review. Issue 7 (29th November 2019) - Coomes, Eric A.; Haghbayan, Hourmazd; Cheema, Asim N.
Abstract: Objective: Systematically review the literature for cardiac catheterization and coronary angiography via distal transradial access (dTRA) and its outcomes. Background: dTRA, via anatomical snuffbox, may have several advantages over conventional transradial access (cTRA) for percutaneous cardiac procedures, including easier left‐sided access for aorto‐coronary grafts, future proximal radial artery preservation, and patient and operator comfort. However, its procedural characteristics and safety profile remain unclear. Methods: Ovid MEDLINE and EMBASE were searched from inception to September 2018. Two authors independently performed two‐stage selection and data extraction. Reports assessing the dTRA approach for cardiac intervention in adults reporting any outcomes were eligible. Descriptive summary statistics were calculated from pooled data. Results: A total of 19 publications comprising 4, 212 participants undergoing dTRA were included. Mean age was 63.8 years, and 23.0% were female. dTRA was primarily undertaken for assessment of stable coronary artery disease (87.6%), with 41.7% for diagnostic procedures and 46.9% undergoing percutaneous coronary intervention. The overall success rate for undertaking the dTRA approach was 95.4% (69–100%). Complications occurred in 2.4% of cases, of which the leading complications were bleeding/hematoma (18.2%). Complication rates did not significantly differ between dTRA and cTRA. The occurrence of radial artery occlusion in patients undergoing dTRA was low (1.7%). Conclusions: Observational data demonstrate that dTRA is a safe and feasible method for percutaneous cardiac procedures, with high rates of procedural success and low rates of complication. As data comparing dTRA with cTRA remain limited, future high‐quality randomized comparative studies are required.